2018
DOI: 10.1007/s11356-018-1408-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of simulated acid rain on fluorine mobility and the bacterial community of phosphogypsum

Abstract: Contamination of soil and water with fluorine (F) leached from phosphogypsum (PG) stacks is a global environmental issue. Millions of tons of PG is produced each year as a by-product of fertilizer manufacture, and in China, weathering is exacerbated by acid rain. In this work, column leaching experiments using simulated acid rain were run to evaluate the mobility of F and the impact of weathering on native bacterial community composition in PG. After a simulated summer rainfall, 2.42-3.05 wt% of the total F co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“… Long et al (2017) also highlighted the capacity of Bacillus to immobilize Sr from aqueous solution by sorption. Fluorine, also present in quite large quantities in this study, can have also detrimental effects on the environment and human health ( Fordyce, 2011 ; Wang et al, 2018 ) and can affect the growth of microorganisms ( Li et al, 2014 ). In our phosphate wastes, various microorganisms were related to strains known to be tolerant to fluorine including Bacillus , Actinobacter , or Pseudomonas ( Wang et al, 2018 , Supplementary Table 6 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… Long et al (2017) also highlighted the capacity of Bacillus to immobilize Sr from aqueous solution by sorption. Fluorine, also present in quite large quantities in this study, can have also detrimental effects on the environment and human health ( Fordyce, 2011 ; Wang et al, 2018 ) and can affect the growth of microorganisms ( Li et al, 2014 ). In our phosphate wastes, various microorganisms were related to strains known to be tolerant to fluorine including Bacillus , Actinobacter , or Pseudomonas ( Wang et al, 2018 , Supplementary Table 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…The structure of the microbial communities analyzed in this study differed from that identified in other studies conducted in phosphate mine wastes, such as in Ragot et al (2013) using T-RFLP and clone libraries to study apatite, the principal phosphate mineral. Next-generation sequencing are generally used to investigate microbial communities in phosphate mining area in China ( Ye et al, 2020 ) and in phosphogypsum in Portugal ( Martins et al, 2016 ), in China ( Wang et al, 2018 ), or in Tunisia ( Zouch et al, 2017 ; ben Mefteh et al, 2019 ; Trifi et al, 2020 ). However, phosphogypsum, the main byproduct of phosphoric acid, obtained after sulfuric acid digestion, present clearly different physicochemical characteristics, compared with phosphate wastes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This not only occupies a large amount of land resources, but also causes phosphorus, fluorine and other pollutants to enter the soil with the leachate, seriously polluting the surrounding ecological environment [2]. The fluorine concentration in the groundwater near the phosphogypsum dump site was 4.13-32.38 mg L −1 , which has exceeded the Quality Standard for Ground Water [3]. Severe fluorosis can lead to abnormal teeth, even endanger bone health and renal function in infants and young children [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive elements present in PG are mainly 226 Ra and its progenies (Haridasan et al 2002). PG is a serious environmental problem and, due to spreading, is able to contaminate locally surface and groundwaters and soil (Rutherford et al 1994;Poole et al 1995;Koopman et al 1999;Haridasan et al 2002;Othman and Al-Masri 2007;Pérez-López et al 2007;Al Attar et al 2011;Jones et al 2012;Ammar et al 2013;Wang et al 2018). The content of radioactive elements in phosphogypsum often exceeds the reference levels regarding 226 Ra concentration established for building materials (European Commission 2000;Borges et al 2013;Hassan 2014).…”
Section: Introductionmentioning
confidence: 99%